Dietary NaNO3, NaCl, K2SO4, or Urea for growing-finishing pigs - Koch, B.A.; Parrish, D.B. (Kansas Agricultural Experiment Station, 2011)
Nitrates are known to harm animals when ingested under certain conditions. Previous work here indicated that a higher level of dietary nitrate might interfere with carotene conversion to Vitamin A. This trial attempted to determine whether such interference does exist and also whether other dietary additives might interfere in carotene conversion.
Keywords: Swine; Nitrates; Additives; Vitamin A